Textual approach to the phenomenon of substitution in modernlinguistic studies (مجلة إحالات, 2026)
The research is interested in presenting an important aspect of the textual linguistic, focusing its attention exactly the concept substitution; witch its process that take place with in the text, falls in the grammatical cohesion, is a parallel function with other foundry methods such as reference, ellipsis and recurrence, so substitution is important technique inthe cohesion of the texts; it may not be enough alone to archive consistency but it is one of the most important means of contributing the part of text and discrimination it from no text.